2017
DOI: 10.1161/jaha.116.003831
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Increases Risk‐Adjusted Morbidity, Mortality, and Cost Following Cardiac Surgery

Abstract: BackgroundDespite the epidemic rise in obesity, few studies have evaluated the effect of obesity on cost following cardiac surgery. We hypothesized that increasing body mass index (BMI) is associated with worse risk‐adjusted outcomes and higher cost.Methods and ResultsMedical records for 13 637 consecutive patients who underwent coronary artery bypass grafting (9702), aortic (1535) or mitral (837) valve surgery, and combined valve–coronary artery bypass grafting (1663) procedures were extracted from a regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 47 publications
3
90
2
8
Order By: Relevance
“…In early postoperative period, ventilation time, ICU and hospital stay were significantly higher in group A. Obesity was found to be associated with prolonged mechanical ventilation [8] and several mechanisms contributed to this. Obese patients had slower return to their consciousness and restoration of the muscle power and many anesthetic agents are fat soluble with prolonged duration of action in obese patients due to redistribution.…”
Section: Ef: Ejection Fractionmentioning
confidence: 85%
See 1 more Smart Citation
“…In early postoperative period, ventilation time, ICU and hospital stay were significantly higher in group A. Obesity was found to be associated with prolonged mechanical ventilation [8] and several mechanisms contributed to this. Obese patients had slower return to their consciousness and restoration of the muscle power and many anesthetic agents are fat soluble with prolonged duration of action in obese patients due to redistribution.…”
Section: Ef: Ejection Fractionmentioning
confidence: 85%
“…Body mass index (BMI) was classified according to the World Health Organization (WHO) into three groups: normal weight (BMI between 18.5 and 24.9 kg/m2), overweight (BMI ≥ 25 Kg/m2 and < 30 Kg/m2), and obese (BMI ≥ 30 Kg/m2) [6,7]. Although higher BMI was associated with major morbidity and increased the cost of healthcare, BMI is not included in several cardiac risk stratification scores [8]. This study aims to evaluate the effect of BMI on early and late morbidity and mortality after CABG in the Egyptian population.…”
Section: Introductionmentioning
confidence: 99%
“…184 Morbidly obese patients have 6.5-fold increase in deep sternal wound infection. 185 Interrogation of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database for abdominal surgery showed that obesity and morbid obesity are independently associated with overall surgical-site infections development in clean and clean-contaminated cases. 186 Further analysis of the same database addressing 16 major cardiovascular, orthopedic and oncologic surgeries showed that morbid obesity significantly increased the odds of wound complications in all surgeries except for pneumonectomy.…”
Section: Wound Infectionmentioning
confidence: 99%
“…Obesity is associated with significant increases in morbidity and mortality, highlighting the urgency for understanding the processes contributing to this epidemic [1,2]. In many of the current environments, highly palatable and affordable food is widely available.…”
Section: Introductionmentioning
confidence: 99%